Teaching Control during the COVID-19 Pandemic. Issue 17 (2022) - Guzmán, J.L.; Žáková, K.; Craig, I.K.; Hägglund, T.; Rivera, D.E.; Normey-Rico, J.E.; Moura-Oliveira, P.; Wang, L.; Serbezov, A.; Sato, T.; Beschi, M.
Abstract: This paper aims to analyze some different solutions that were adopted in control education activities during the pandemic. The authors of this paper are educators in the control education field from different countries on all the continents, who have developed a questionnaire with the idea of collecting data about the COVID-19 pandemic impact on the control education activities. The main objective is to study the diverse alternatives that were used worldwide to perform the online educational activities during that period, such as methodologies, tools, learning management systems (LMS), theoretical exercises, laboratory experiments, types of exams, simulators, software for online lecturing, etc. As a result, comparisons between pre-and during-pandemic educational resources and methods are performed, where useful ideas and discussions are given for the control education community.